Factors Related to Work Fatigue in Production Employees at PT.Y Rubber in 2024 - Maretta, Rezi; Kalsum, Ummi; Aswin, Budi (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Production employees are at high risk of experiencing work fatigue due to the physical and psychosocial demands inherent in their work activities. Work fatigue can negatively impact productivity, safety, and the health of the employees themselves. Purpose: This study aims to analyze the relationship between knowledge, work of period, implementation of safety talk and safety climate with safety behavior in workers at PT. X PKS Y.  Method: The research design is quantitative with a cross-sectional research design. The population in this study is all workers in the production area of PT. Y Rubber Jambi is 68 people. The sample in this study amounted to 58 people. Result and Discussion: Work fatigue for production employees at PT. Y Rubber Jambi by 62.1%. Factors related to work fatigue were age (p-value=0.002), work attitude (p-value=0.000), workload (p-value=0.03), and length of work (p-value=0.02). As for the noise and lighting variables, it has not been proven to be statistically significant. There was no publication bias on each variable analyzed. Conclusion: Work fatigue among production employees at PT. Y Rubber is influenced by several factors, including age, work attitude, workload, and duration of working hours